Interpretation of HRQoL in Children with Thalassemia Major and Healthy Children From an Islamic Perspective - Andi Nurul Madinah; Karimulloh Karimulloh (Jurnal Multidisiplin Ibrahimy, 2026)
Thalassaemia has been proclaimed a global health challenge by the World Health Organization (WHO) due to its presence in many areas of the world. Challenges faced by children with thalassaemia include physical, psychological, social and academic difficulties that affect their Health-Related Quality of Life (HRQoL). However, the HRQoL from Islamic perspective is not only seen from physical, social, and psychological aspects, but also spiritual and moral aspects. The present study aimed to explore the Islamic view of the differences in Health-Related Quality of Life (HRQoL) between children with thalassaemia major and healthy children. This study uses a library research method, which is a comprehensive review of the literature sources. The findings indicate that the conditions experienced by children with major thalassemia and healthy children can be understood as part of Allah’s divine decree, which contains wisdom and meaning. Islam emphasizes that a person’s value before Allah is not determined by physical, psychological, or social perfection, but rather by their piety and deeds. Accordingly, this study is expected to contribute to healthcare professionals, educators, and parents or caregivers by encouraging them to consider not only children’s physical and psychological conditions but also their spiritual well-being and sense of meaning in life.